The Influence of Leadership and Work Environment on the Performance of Employees of the Manpower and Transmigration Service of Karawang Regency - Icha Nurfadilah Anwar; Suroso Suroso; Flora Patricia Anggela (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of leadership and work environment on employee performance at the Manpower and Transmigration Office of Karawang Regency, both partially and simultaneously. Using a quantitative approach, the sample used was a purposive sampling technique, as many as 100 employees of the Manpower and Transmigration Office of Karawang Regency and analyzed by multiple linear regression with SPSS version 25. The results showed that leadership has a significant positive influence on employee performance with a t-count of 4,687> 1,966 t-table and a significant value of 0.00 <0.05, while the work environment does not have a significant influence on employee performance with a t-count of 1.859 <1.966 t-table and a significance value of 0.66> 0.05. Simultaneously, leadership and work environment have a positive effect on employee performance with an f-count of 28.953> 2.627 f-table. Leadership is the main factor in appreciating and encouraging employees to work according to their responsibilities. For further research, it is suggested to expand the scope of government as a whole to provide a deeper influence on employee performance